A method for C2 acylation of 1, 3-indandiones. Issue 22 (31st May 2018) - Larsen, Brian J.; Rosano, Robert J.; Ford-Hutchinson, Thomas A.; Reitz, Allen B.; Wrobel, Jay E.
Abstract: The 1, 3-indandione scaffold is an important structural motif used in the preparation of a large number of industrial chemical and pharmaceutical compounds. However, few approaches allow for the direct C2 acylation on these building blocks. A method was developed using DMAP and EDCI, which is mild in reactivity, covers a diverse range of carboxylic acid acylating agents, is compatible with electron releasing and withdrawing substituents on the 1, 3-indandione partner, and performs well in a polar aprotic solvent (for solubility reasons) This method cleanly afforded twenty five different products in yields of 32–96%. Graphical abstract: Image 1